2020
DOI: 10.1002/cite.202000052
|View full text |Cite
|
Sign up to set email alerts
|

Plasmachemical Trace‐Oxygen Removal in a Coke Oven Gas with a Coaxial Packed‐Bed‐DBD Reactor

Abstract: The trace‐O2 removal in coke oven gas, which enables better utilization of its contained H2, is investigated with combinations of atmospheric nonthermal plasma and a Pt/γ‐Al2O3 catalyst. Herein it is shown that a coaxial packed‐bed dielectric barrier discharge (DBD) reactor removes up to 80 % O2 in a model coke oven gas. Along this line, the H2 content and the usage of Al2O3 granules in the plasma zone have been identified as major factors for the plasmachemical trace‐O2 conversion. In contrast to the Pt/γ‐Al2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In previous works, it has already been shown that non‐thermal plasma generated in a glass reactor is suitable for the conversion of oxygen at volume flow rates of 0.1 mN 3 h-1 with changes of the coke oven gas composition below the measurement accuracy of the analytics (< 1 vol %) indicating no high selectivity for other potential concurrence reactions as the hydrogenation of N 2 , CO, or CO 2 9, 10. The next important step to industrial application is the further development based on the proven glass reactor concept.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, it has already been shown that non‐thermal plasma generated in a glass reactor is suitable for the conversion of oxygen at volume flow rates of 0.1 mN 3 h-1 with changes of the coke oven gas composition below the measurement accuracy of the analytics (< 1 vol %) indicating no high selectivity for other potential concurrence reactions as the hydrogenation of N 2 , CO, or CO 2 9, 10. The next important step to industrial application is the further development based on the proven glass reactor concept.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has already confirmed the application range of non-thermal plasma in various conversion processes [5][6][7][8]. Furthermore, the fundamental feasibility of non-thermal plasma (NTP) for the oxygen removal in COG with reactors based on the dielectric barrier discharge (DBD) has already been proven [9,10]. Nevertheless, further investigations are necessary to determine the applicability of NTP for oxygen removal in COG at industrial scale.…”
Section: The Project Carbon2chem and The Role Of Plasma Within Itmentioning
confidence: 99%
“…A thermal conductivity detector is used to detect H 2 , while infrared cells are applied for the detection of CO, CO 2 and CH 4 and an electrochemical sensor is used for O 2 detection. With this experimental setup the technical feasibility for the deoxygenation of an artificial COG has been successfully proven [27,28]. However, scale-up of the glass reactor is limited with respect to its maximum volume flow as well as operation at increased pressure.…”
Section: Gas Cleaning and Conditioning Of Steel Mill Process Gasesmentioning
confidence: 99%
“…Before entering the system boundaries, the catalyst‐deactivating trace components, such as sulfur and oxygen, are eliminated, e.g., with electric swing adsorption or plasma catalytic processes . The conversion of trace components has a negligible influence on the overall CO 2 balance and, thus, will not be taken into account in the model.…”
Section: Case Definitionmentioning
confidence: 99%